2019
DOI: 10.1186/s12913-018-3825-z
|View full text |Cite
|
Sign up to set email alerts
|

Influences on the access to and use of formal community care by people with dementia and their informal caregivers: a scoping review

Abstract: BackgroundThe literature describes the obstacles to sufficient care faced by people with dementia and their informal caregivers. Although factors influencing access and utilisation are frequently studied, the body of knowledge lacks an overview of aspects related to influence. The frequently used Behavioural Model of Health Care Use (BM) could be used to structure and explain these aspects. An adaptation of the BM emphasises psychosocial influences and appears to enrich the understanding of the use of long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(121 citation statements)
references
References 146 publications
(521 reference statements)
5
108
2
6
Order By: Relevance
“…Lack of knowledge of services is not unique to rural areas, and in fact has been identified in the broader literature as a significant barrier to dementia service provision (Macleod et al, 2017;Phillipson, Jones, & Magee, 2014;Robinson et al, 2009;Sutcliffe, Roe, Jasper, Jolley, & Challis, 2013). Similarly, perceptions of services as inflexible, inappropriate for needs, and not tailored or person-centred are barriers regardless of rurality, as are some of the values and beliefs around caregiving (guilt, reluctance to ask for assistance) and care recipient resistance (Bieber, Nguyen, Meyer, & Stephan, 2019;Boots, Wolfs, Verhey, Kempen, & de Vugt, 2015;Brodaty et al, 2005;Greenwood & Smith, 2015;Macleod et al, 2017;Phillipson & Jones, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Lack of knowledge of services is not unique to rural areas, and in fact has been identified in the broader literature as a significant barrier to dementia service provision (Macleod et al, 2017;Phillipson, Jones, & Magee, 2014;Robinson et al, 2009;Sutcliffe, Roe, Jasper, Jolley, & Challis, 2013). Similarly, perceptions of services as inflexible, inappropriate for needs, and not tailored or person-centred are barriers regardless of rurality, as are some of the values and beliefs around caregiving (guilt, reluctance to ask for assistance) and care recipient resistance (Bieber, Nguyen, Meyer, & Stephan, 2019;Boots, Wolfs, Verhey, Kempen, & de Vugt, 2015;Brodaty et al, 2005;Greenwood & Smith, 2015;Macleod et al, 2017;Phillipson & Jones, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous research suggests that informal caregivers may receive little education or knowledge support from primary care physicians, despite considering physicians the most reliable, trustworthy sources for information about the caregiving process . Similarly, evidence suggests that lack of dementia knowledge among informal caregivers may act as a barrier to accessing formal community care, potentially leading to worse outcomes for both caregivers and their family members with dementia. Furthermore, previous evidence suggests increasing both formal and informal caregivers’ knowledge domains (e.g., behavior management, disease management/progression, communication) can lead to improved ability to care and better outcomes in care receivers.…”
Section: Discussionmentioning
confidence: 99%
“…They regarded their caregiver status as a natural continuation of a long marriage. These spousal caregivers echoed research that reported that they played an immensely important role, from a humane perspective and economic point of view, as they supplement the provision of formal community care [29].…”
Section: Discussionmentioning
confidence: 57%